"I'm Not a Number, I'm a Human Being:" A Phenomenological Study of Women's Responses to Labeling. (April 2021) - Boppre, Breanna; Reed, Shon M.
Since the 1970s, the number of women under correctional supervision has risen drastically. With the increase in women's system-involvement, it is important to consider the impact that crime-focused labels may have on women's self-perceptions and reentry. This study applies a feminist lens to labeling theory. Through phenomenological interviews and focus groups with 19 women under community supervision in a Northwestern State, women's responses were analyzed using thematic analysis. Four major themes emerged highlighting the distinct contexts of women's responses to labels and the impacts of such labels on their lives. Theoretical and policy implications are discussed.